PERANCANGAN MEDIA ILUSTRASI 2D PADA DAMPAK FEAR OF MISSING OUT - Pagi, Akalili Mentari; Fauzi, Muhammad (Fakultas Seni Rupa dan Desain, Institut Seni Indonesia Surakarta, 2024)
Social media provide some content that we always looking for rather than conventional media. Nowadays, social media could be a freedom of speech media and expression platform. However, social media can also have negative impacts, such as contributing to mental health problems and the development of fear of missing out on illness (FOMO). FOMO, or Fear of Missing Out, is a sensation of anxiety or worry that arises when someone feels unaware of or excluded from important information, events, experiences, trends, and so on. Social media exacerbates the severity of FOMO. Individuals with FOMO disorder constantly experience feelings of inadequacy in their lives, causing them to constantly scroll through social media platforms and compare their own experiences to those of others. Animation is the process of manipulating static figures to create the illusion of movement. Currently, animation has emerged as a promotional medium that is very effective, visually attractive and easy to understand. Illustration refers to the act of embellishing, interpreting, or visually explaining a text, concept, or process, with the aim of incorporating it into printed and digitally produced media